Clinical Profile and Fetomaternal Outcomes of Placenta Previa In Scarred Uterus in a Tertiary Hospital in Chattogram, Bangladesh - Chawdhury, Shahnaj Jahan; Sultana, Nahid; Shirin, Fahmida; Sultana, Munawar (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Placenta Previa (PP) is a significant cause of management challenges for obstetricians, with a greater challenge and risk when a PP occurs in a pregnancy with a previous uterine scar. Evidence of the complications associated with the occurrence of these two risk factors together is scarce in Bangladesh. This study aimed to describe PP's clinical profile and fetomaternal outcome coexisting with a previous uterine scar in a public teaching tertiary-level hospital in Chattogram, Bangladesh. Materials and methods: A prospective observational study was conducted from January 2024 to June 2024 in Chittagong Medical College Hospital. Consecutively admitted 38 singleton pregnancies with PP with a history of Cesarean Section (CS) or myomectomy were included. Information was collected using a structured case record form and analyzed using MS Excel. Results: The mean age of the patients was 29.5±5.4 (Range: 18 to 42) years. The mean value of the parity and gestational age was 3.42±1.41 and 35.08±2.59 weeks, respectively. Thirty-seven (97.4%) had cesarean scar, and the mean number of CS was 1.95± 0.89. Placenta accreta spectrum was present in 25 (65.8%) patients, and in 23 (60.5%) patients, PP was covering the uterine scar. Twenty-eight (73.7%) patients developed haemorrhage, 15.8% developed shock, 44.7% required ³3 unit blood transfusion, 15.8% had bladder injury, 39.5% required a peripartum hysterectomy and the maternal mortality rate was 7.9%. According to the fetal outcome, NICU admission was 47.7%, perinatal death was 18.4%, and a low Apgar score at 5 minutes was observed in 71.1% of neonates. Conclusion: PP in the scared uterus is associated with diverse maternal and neonatal complications. Therefore, careful monitoring, planning, and resource allocation for delivery are crucial in such cases to manage potential risks effectively. JCMCTA 2025 ; 36 (1) : 14-17